Analysis The Application of Health, Safety and Work Environment on Employee Performance at Oilfield Services Companies in Indonesia 2023 - Muhammad Raditya Nur Ihsan; Rehani Fitrina; Siti Krisnawati; Bramastya Faris Rasyad Ahmad (Green Publisher, 2025)
This study, was conducted at Oilfield Services Companies in 2023, analyzing the application of Health, Safety, and Work Environment (HSE) on employee performance. Utilizing quantitative methodology and questionnaires for data collection, the research aims to justify the correlation between HSE practices and working conditions with employee performance. It analyzes the effects of HSE implementation, evaluates key productivity influencers, and provides improvement recommendations. The findings are valuable for company management, aiding in HSE implementation enhancement and fostering an environment conducive to optimal employee performance. The research potentially serves as a guide for similar companies striving for improved employee well-being and operational efficiency. Analysis results affirm a positive and significant HSE implementation impact on employee performance, with high Cronbach Alpha values (X1 = 0.815, X2 = 0.882, Y = 0.841), emphasizing the role of factors like high-quality HSE training, safe equipment, and comfortable working conditions.